Seismic hazard in deep hard rock mining: a brief comparison of stoping and caving experience - Xu, Y-H; Ollila, B; Parsons, J; Joughin, W; Meyer, SG; Jakubec, J; Thomas, A (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
As global mineral resources become depleted near the surface, hard rock mining operations are progressing to depths exceeding 1 km metres and approaching ultra-depths of 2 to 3 km or greater, resulting in an escalating seismic hazard. This paper presents a comparative discussion of seismic mechanisms and risk management strategies between deep hard rock stoping and caving mines. First, common mining-induced seismic source mechanisms between these two mining methods are reviewed based on case studies that focus on strong rockburst events. Accordingly, their risk mitigation measures from a practical ground control perspective were compared and discussed. The goal of this paper is to identify first principles that can guide seismic risk management plans for both mining methods.